1988
DOI: 10.1021/tx00004a009
|View full text |Cite
|
Sign up to set email alerts
|

Leurosine biotransformations: an unusual ring-fission reaction catalyzed by peroxidase

Abstract: The dimeric Vinca alkaloid leurosine undergoes an unusual fission of the piperidine ring of the Iboga substructure when reacted with horseradish peroxidase and hydrogen peroxide. A preparative-scale oxidation of leurosine provided 15'-hydroxycatharinine, which was identified by infrared and proton and carbon-13 NMR spectroscopies and high-resolution mass spectrometry. A proposed pathway for the formation of 15'-hydroxycatharinine involves radical and iminium intermediates and cleavages of a putative diol. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…5A). An analogous oxidative biotransformation pathway has also been reported for leurosine, another dimeric Vinca alkaloid, when it was catalyzed by horseradish peroxidase (Goswami et al, 1988). Furthermore, a similar compound, catharinine, has been reported as a natural product from several Catharanthus species (Andriamialisoa et al, 1978) as a result of the C-13 and C-14 bond fission of the piperidine ring, probably following the same metabolic reaction from an appropriate precursor in plants.…”
Section: Selective Metabolism Of Vincristine By Cyp3a5 In Vitromentioning
confidence: 61%
“…5A). An analogous oxidative biotransformation pathway has also been reported for leurosine, another dimeric Vinca alkaloid, when it was catalyzed by horseradish peroxidase (Goswami et al, 1988). Furthermore, a similar compound, catharinine, has been reported as a natural product from several Catharanthus species (Andriamialisoa et al, 1978) as a result of the C-13 and C-14 bond fission of the piperidine ring, probably following the same metabolic reaction from an appropriate precursor in plants.…”
Section: Selective Metabolism Of Vincristine By Cyp3a5 In Vitromentioning
confidence: 61%
“…In addition to the works discussed above in some detail, in many studies mass spectrometry was used only to provide an elemental composition for the given molecular weight derived from HR-EI-MS measurements or to list the main fragments as a fingerprint pattern without giving any structural explanation [29][30][31][32][33][34].…”
Section: Ei-ms Analysismentioning
confidence: 99%
“…In many of these studies no spectroscopic discussion was reported, only an enumeration of some characteristic 1 H peaks of the biosynthetic products [69], or partial 1 H and 13 C assignments were given [34]. In some other cases NMR spectroscopy served as an indispensable tool to understand the reaction mechanisms.…”
Section: Historical Examples Of Bisindole Structure Identification Bymentioning
confidence: 99%
See 2 more Smart Citations